2018
DOI: 10.1080/15384101.2018.1440879
|View full text |Cite
|
Sign up to set email alerts
|

NEDD4 promotes cell growth and motility in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common causes of cancer-related death worldwide. In China, the situation is even worse as cancer incidence and mortality continue to increase rapidly. Although tremendous progress has been made toward HCC treatments, the benefits for liver cancer patients are still limited. Therefore, it is necessary to identify and develop novel therapeutic methods. Neuronally expressed developmentally downregulated 4 (NEDD4), an E3 ubiquitin ligase, plays a critical role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
(61 reference statements)
2
14
1
Order By: Relevance
“…Cumulative evidence suggests that NEDD4 is linked to tumor progression in several human cancers, such as gastric carcinoma, hepatoma carcinoma, bladder cancer, and prostate cancer [25, 32, 33, 38]. Based on our studies, NEDD4 expression gradually increases in line with BC progression, from normal tissues, DCIS, IDC without lymph node metastasis to BCLNM tumors, which is a well-established clinical model for BC progression [5].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Cumulative evidence suggests that NEDD4 is linked to tumor progression in several human cancers, such as gastric carcinoma, hepatoma carcinoma, bladder cancer, and prostate cancer [25, 32, 33, 38]. Based on our studies, NEDD4 expression gradually increases in line with BC progression, from normal tissues, DCIS, IDC without lymph node metastasis to BCLNM tumors, which is a well-established clinical model for BC progression [5].…”
Section: Discussionsupporting
confidence: 51%
“…NEDD4 has a role in promoting the growth of hepatocellular [32] and bladder cancer cell lines [33]. To determine the role of NEDD4 in BC growth, we first examined how NEDD4 expression affects cell growth using BC cell lines from different BC subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic inflammation infection, mainly caused by hepatitis B virus (HBV) or hepatitis C virus (HCV), has been proposed as a causative mechanism in HCC carcinogenesis 4 . Although the diagnosis and treatment methods of HCC have been developing, exairesis is still the first line and most effective treatment to HCC 5 . What is frustrating is that the recurrence and mortality of HCC is still high because of the extensive characteristics of HCC, including intrahepatic metastasis, venous invasion, and distant metastasis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…NEDD4-1 contains four WW domains and is an ancestral member of the NEDD4 family ( 23 ). Previous studies have indicated that NEDD4-1 is frequently overexpressed in several types of human cancers, including hepatocellular carcinoma, lung cancer and gastrointestinal cancer ( 128 130 ). A range of tumor suppressors can be ubiquitinated by NEDD4-1, including PTEN, c-Myc and large tumor suppressor kinase 1 ( 128 , 131 ).…”
Section: Structure and Function Of Hect-type E3 Ligases In Gcmentioning
confidence: 99%
“…Previous studies have indicated that NEDD4-1 is frequently overexpressed in several types of human cancers, including hepatocellular carcinoma, lung cancer and gastrointestinal cancer ( 128 130 ). A range of tumor suppressors can be ubiquitinated by NEDD4-1, including PTEN, c-Myc and large tumor suppressor kinase 1 ( 128 , 131 ). Immunohistochemical analysis conducted by Kim et al ( 130 ) showed that NEDD4-1 is overexpressed in colorectal and gastric carcinomas.…”
Section: Structure and Function Of Hect-type E3 Ligases In Gcmentioning
confidence: 99%